Exploring Factors Influencing Digital Transparency in Local Governments: Practices in Indonesia - Octavio, Muhammad Fadhly Rizky; Urumsah, Dekar (Jurnal Dinamika Akuntansi dan Bisnis, 2024)
This study aims to analyze the factors that influence digital transparency in Indonesian local governments. The tested determinants are e-government maturity, financial report quality, and local government accountability systems. Data were collected from official websites, accountability reports, and financial reports of 541 Indonesian provincial and district/ city government. Using multiple regression analysis, this study found that e-government maturity, financial report quality, and local government accountability systems significantly positively affect digital transparency. The findings indicate that good governance practices can encourage transparency in presenting financial and non-financial information. However, this study also found that some local government websites are not fully accessible, which may hinder access to necessary data. The implications of this study emphasize the importance of developing mature e-government, improving the quality of financial reports, and strengthening accountability systems in local governments to strengthen transparency, reduce corruption, and increase government legitimacy.